2018
DOI: 10.1039/c8dt00984h
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination-promoted skeletal transformation of IPR C76 discovered via trifluoromethylation under the formation of non-IPR C76(CF3)nFm

Abstract: High-temperature chlorination of an Isolated-Pentagon Rule (IPR) D2-C76 fullerene followed by high-temperature trifluoromethylation of non-IPR C76 chlorides with CF3I unexpectedly resulted in a series of non-IPR C76(CF3)nFm compounds. X-ray diffraction study with the use of synchrotron radiation revealed the mixed CF3/F structures of non-classical, non-IPR C76(CF3)14, C76(CF3)14F2, and C76(CF3)16F6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 29 publications
3
37
0
3
Order By: Relevance
“…It was recently shown that C 60 is also capable to skeletal transformations when the interaction is carried out at harsher conditions of 420–440 °C . As the further development of the method, two‐stage process, a chlorination followed by trifluoromethylation (Cl/CF 3 ), was proposed . Using the two‐stage method, some CF 3 derivatives of non‐IPR or non‐classical fullerenes have been isolated in the cases of C 60 and C 76 (1) (the numeral in parentheses indicates the number of isomer according to the spiral algorithm).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…It was recently shown that C 60 is also capable to skeletal transformations when the interaction is carried out at harsher conditions of 420–440 °C . As the further development of the method, two‐stage process, a chlorination followed by trifluoromethylation (Cl/CF 3 ), was proposed . Using the two‐stage method, some CF 3 derivatives of non‐IPR or non‐classical fullerenes have been isolated in the cases of C 60 and C 76 (1) (the numeral in parentheses indicates the number of isomer according to the spiral algorithm).…”
Section: Figurementioning
confidence: 99%
“…). This type of chlorination‐promoted skeletal transformations has been reported for C 60 and some isomers of higher fullerenes such as C 76 (1), C 78 (2), and C 100 (18) . Usually, the SWR transformations occurred, if one or both carbon atoms of a rotating C−C bond are chlorinated.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[42] 3.2.5. C 76 [133] 3.2.6. C 82 ,C 84 [51] Es wurde postuliert, dass diese beiden nichtklassischen Nicht-IPR-Chloride von C 84 aus zwei unterschiedlichen C 86 -basierten nichtklassischen Nicht-IPR-Fullerenchlorid-Vorstufen hervorgehen:( NC)C 86 Cl 24 und (NC)C 86 Cl 26 .B ei (NC)C 86 Cl 26 ist der einzige Siebenring in der Mitte der beiden DFP-Paare wie bei einem Sandwich angeordnet, was eine Folge der Abspaltung einer C 2 -Einheit der Fünfring-Sechsring-Verknüpfungsstellen innerhalb des ursprünglichen IPR-Käfigs C 2 (33)-C 88 ist.…”
unclassified